انتشار التعليم الأهلي: دراسة جغرافية تحليلية لعوامل ظهوره وانتشاره وكفاءته الوظيفية في مدينة بغداد - Sinai Adnan Abdullah; Areej Bahjat Ahmed (College of Education for Women, 2021)
The research aims to assess the functional efficiency of private education institutions when performing their task at a high level to satisfy the needs of the city's residents. It has been recently noticed that people favor private education to government institutions education; a matter which has led to the phenomenon of its spread, and to access its consequences. Its spread has competed not only the governmental institutions, but also the private institutions among themselves in providing the best educational services and survive accordingly. The present paper further examines the pressing negative side on the teaching faculty, especially with regard to their monthly income. The positive and negative points altogether have made it urgent to find the best and proper solutions to enhance faculty members' output, and increase their positive sides to serve the educational service. Such steps cannot be achieved without conducting tests inside these private educational institutions to interpret all their scientific queries. The study has used the descriptive, functional and analytical approach, and adopted a field study by collecting relevant data and information for the purpose of the research and its problem based on the reality of the facilities of this service for the year (2020). The first two questionnaire forms were distributed to a sample of (1520) parents of students in private schools, by taking one student per family. The second sample amounted to (200) survey forms distributed to the teaching faculty. Results have shown that the high percentage of students registered in the primary stage greatly surpassed the rest of the educational stages. Besides, the increase in the educational level provided by these institutions is the reason for its spread; that is why, the level of students' parents' satisfaction has increased to (good) level.